Electronic medical record development strategy: Counseling based on SWOT analysis and digital maturity - Ningsih, Kori Puspita; Markus, Suryo Nugroho; Rahmani, Ngatoiatu; Santoso, Sugeng; Saputro, Agung Dwi (Universitas Muhammadiyah Magelang, 2025)
The Minister of Health Regulation (PMK) Number 24 of 2022 mandates healthcare facilities, including hospitals, to implement Electronic Medical Records (EMR). However, the optimal development of EMR remains a challenge. This community service aims to provide counseling on EMR development strategies based on SWOT analysis and digital maturity. This activity is a dissemination of research findings conducted in 2022 regarding EMR development. The method used was community education through counseling provided to the heads of departments and medical record staff of Bethesda Hospital regarding EMR development strategies. The evaluation results showed that Bethesda Hospital’s digital maturity level is at level 4 (EMRAM). Therefore, a more aggressive EMR development strategy is recommended, leveraging existing strengths and opportunities, to enhance the digital maturity level of EMR to support clinical decision-making and patient safety.